PEMANFAATAN KULIT PISANG KEPOK SEBAGAI ADSORBEN ZAT ORGANIK PADA AIR GAMBUT DENGAN VARIASI WAKTU PENGADUKAN - Mahwar Qurbaniah (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTThe functional groups that act as adsorbent in kepok banana peel (Musa acuminate L.) can be identified are -OH, -COO, and -NH. Products in the form of a biological charcoal adsorbent from kepok banana peel can increase the economic value of a banana peel. This research aimed to study of using the kepok banana peel sour as adsorbent for reducing the content of organic matter in peat water. Parameter observed was the shaking time. Kepok banana peel that has been obtained from industrial waste bananas fried in Pontianak burned to charcoal. Activated charcoal that has been obtained with a solution of 0.1 M NaOH,washed with 0.1% HCl and distilled water and then dried to constant weight. Furthermore, biological charcoal from kepok banana peels used as adsorbent to reduce the content of organic matter in peat water which measured to decrease the color intensity of peat water (absorbance measurement) by using UV-VIS spectrophotometer in the wavelength of 254 nm. The results showed that decreasing in organic matter content in 70 mL of water peat obtained in 1 gram of adsorbent was 60 minutes. This results showed that the adsorbent of kepok banana peel can reduce water content of organic matter in peat water.Keywords: adsorbents, peat water, kepok banana peel (Musa acuminate L.)